Method for producing hydrophobic silica aerogel felt, and silica aerogel felt

During the preparation of silica aerogel felt, the surface modification was performed using water glass solution and acid mixture aqueous solution, and the problem of residual chlorine and low surface modification efficiency was solved, thereby achieving high hydrophobicity and thermal insulation properties. Preparation of silica aerogel felt.

CN119403761APending Publication Date: 2025-02-07LG CHEM LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380048782.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-22
Filing Date
2023-07-21
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing silica aerogel felt has residual chlorine problems during the preparation process, which leads to corrosion problems and is not very effective in surface modification, which affects its hydrophobicity and thermal insulation properties.

Method used

Using a method, the surface is performed using alkyldisiloxane compounds by preparing a silica sol containing a water glass solution and impregnating it into a felt substrate, followed by surface modification in an aqueous acid mixture solution. Modify to ensure that the concentration of acetic acid and nitric acid is between 30% and 90% and 5% to 10%, avoiding the use of chlorine-containing compounds.

Benefits of technology

The preparation of silica aerogel felt without residual chlorine is achieved, with excellent surface modification efficiency and high hydrophobicity, improving its thermal insulation performance and stability, and is suitable for various industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200362160000051
    Figure BDA0005200362160000051
  • Figure BDA0005200362160000091
    Figure BDA0005200362160000091
  • Figure BDA0005200362160000141
    Figure BDA0005200362160000141
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a silica aerogel felt having excellent surface modification efficiency and high hydrophobicity while not containing residual chlorine, and a silica aerogel felt not containing residual chlorine manufactured thereby.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of Korean Patent Application No. 10-2022-0091299 filed in the Korean Intellectual Property Office on July 22, 2022, the entire contents of which are incorporated herein by reference in their entirety.

[0002] The present invention relates to a method for producing a silica aerogel felt which does not contain residual chlorine and has excellent surface modification efficiency and high hydrophobicity, and a silica aerogel felt which does not contain residual chlorine produced thereby. Background Art

[0003] Aerogel is a super porous, high specific surface area (≥500m 2 / g) of a material with a porosity of about 90% to 99.9% and a pore size in the range of 1nm to 100nm, and is a material with excellent properties such as ultra-lightweight, ultra-insulating and ultra-low dielectric properties. Therefore, research on the development of aerogel materials and their practical use as transparent thermal insulation materials, environmentally friendly high-temperature thermal insulation materials, ultra-low dielectric films for highly integrated devices, catalysts and catalyst carriers, electrodes for supercapacitors, and electrode materials for seawater desalination has been actively conducted.

[0004] The biggest advantage of aerogel is that it has super thermal insulation, and its thermal conductivity is below 0.300W / m·K, which is lower than the thermal conductivity of organic thermal insulation materials such as traditional polystyrene foam. In addition, the fatal weakness of organic thermal insulation materials, such as fire vulnerability and the generation of harmful gases during fire, can also be solved.

[0005] However, due to its complicated preparation process and high preparation cost, aerogel is only used for extremely limited purposes despite its excellent material properties. In addition, due to its high porosity, the mechanical strength of aerogel is very poor, so there is a disadvantage that aerogel is easily broken even by a slight impact. Therefore, in recent years, aerogel felt composite technology has been studied to make up for the above shortcomings of aerogel itself and enable processing in various forms.

[0006] Aerogel felt is an aerogel material that has been compounded and manufactured in the form of a mat or sheet, and has the property of being bendable, foldable or cut due to its flexibility. Therefore, aerogel felt can be applied to pipe insulation or clothing, etc., and its various industrial applications are also feasible. Aerogel felt is flexible because it is a composite composed of fibers and aerogel. The fibers are used to enhance the flexibility and mechanical strength of the aerogel felt, and the aerogel imparts thermal insulation properties due to its porosity. The key composite technology of aerogel felt is to composite the characteristics of the fibers with those of the aerogel to enhance the advantages of the fibers and aerogel and compensate for their shortcomings.

[0007] This aerogel felt is a new material that is superior to polystyrene foam or polyurethane foam, which are traditional polymer insulation materials, in terms of heat resistance and thermal insulation. It is attracting attention as a high-tech material that can solve energy-saving and environmental problems in the future.

[0008] The silica aerogel felt is manufactured by the following process: gelation is performed by mixing the fiber with the silica sol obtained from water glass or an alkoxide precursor, followed by aging, surface modification and drying, wherein the surface modification is performed by adding an acid catalyst and a hydrophobic agent after the silica sol is impregnated into the fiber. At this time, the hydrophobic agent is not miscible with water and therefore has no reactivity with the wet gel, particularly the hydrogel obtained by gelling the water glass, so a method of solvent replacement with an amphiphilic organic solvent such as ethanol has been used, or a method of using a trimethylchlorosilane (TMCS) hydrophobic agent and reacting using the HCl generated therefrom as a catalyst has been used, but the solvent replacement with an amphiphilic organic solvent requires a long solvent replacement time and generates a large amount of diluted organic solvent, and the method using the trimethylchlorosilane (TMCS) hydrophobic agent generates HCl, resulting in Cl remaining in the final silica aerogel felt.

[0009] Since residual chlorine in silica aerogel felt can cause corrosion, it is necessary to develop a method for manufacturing silica aerogel felt having high hydrophobicity by a method having excellent surface modification efficiency but not generating residual chlorine.

[0010] [Prior art literature]

[0011] [Patent Document]

[0012] (Patent Document 1) US 5,789,075 B Summary of the invention

[0013] Technical issues

[0014] An object of the present invention is to provide a method for manufacturing a silica aerogel felt, wherein the silica aerogel felt has excellent surface modification efficiency and does not contain residual chlorine, which eliminates corrosion problems that may be caused when the silica aerogel felt is used, thereby showing excellent stability.

[0015] Another object of the present invention is to provide a chlorine-free silica aerogel felt.

[0016] Technical Solution

[0017] In order to achieve the above object, the present invention provides a method for manufacturing a silica aerogel felt and a silica aerogel felt.

[0018] [1] The present invention provides a method for manufacturing a silica aerogel felt, the method comprising: 1) preparing a silica sol containing a water glass solution; 2) impregnating the silica sol into a felt substrate; 3) preparing a wet gel by gelling the silica sol while the silica sol is impregnated into the felt substrate; 4) immersing the wet gel in an acid mixture aqueous solution containing an acetic acid and nitric acid aqueous solution, and surface-modifying the wet gel with an alkyl disiloxane compound; and 5) drying the surface-modified wet gel, wherein after the above step 4), the acetic acid concentration (w / w) is 30% to 90%, and the nitric acid concentration (w / w) is 5% to 10%.

[0019] [2] In the above [1], the present invention provides a method for producing a silica aerogel felt, wherein the acetic acid concentration (w / w) is 35% to 80%.

[0020] [3] In the above [1] or [2], the present invention provides a method for producing a silica aerogel felt, wherein the concentration (w / w) of nitric acid is 5% to 10%.

[0021] [4] In any one of the above [1] to [3], the present invention provides a method for manufacturing a silica aerogel felt, wherein, in the above step 4), after the process of immersing the wet gel in the acid mixture aqueous solution is completed, the process of surface modification with the alkyl disiloxane compound is sequentially carried out.

[0022] [5] In any one of the above [1] to [4], the present invention provides a method for manufacturing a silica aerogel felt, wherein, in the above step 4), the acid mixture aqueous solution and the alkyl disiloxane compound are introduced into the wet gel in sequence, or the acid mixture aqueous solution and the alkyl disiloxane compound are introduced into the wet gel at the same time.

[0023] [6] In any one of the above [1] to [5], the present invention provides a method for manufacturing a silica aerogel felt, wherein, in the above step 4), the alkyl disiloxane compound is added in a volume ratio of 1 to 3 times based on the volume of the wet gel.

[0024] [7] In any one of the above [1] to [6], the present invention provides a method for producing a silica aerogel felt, wherein the alkyl disiloxane compound is hexa(C 1-8 alkyl) disiloxane.

[0025] [8] In any one of the above [1] to [7], the present invention provides a method for producing a silica aerogel felt, wherein the method for producing a silica aerogel felt is carried out under chlorine-free conditions.

[0026] [9] The present invention provides a silica aerogel felt having a thermal conductivity of 12 mW / mK to 19 mW / mK and a Cl content of 0 ppm to 500 ppm.

[0027]

[10] In the above [9], the present invention provides a silica aerogel felt, wherein the silica aerogel felt has a Cl content of 0 ppm to 200 ppm.

[0028] Beneficial Effects

[0029] The method for producing a hydrophobic silica aerogel of the present invention can produce a silica aerogel felt having excellent surface modification efficiency and high hydrophobicity while containing no residual chlorine, and can therefore be usefully applied to industries requiring it, particularly industries requiring a silica aerogel having high hydrophobicity or industries requiring a silica aerogel having a hydrophobicity in a variety of ranges. DETAILED DESCRIPTION

[0030] Hereinafter, the present invention will be described in more detail to facilitate understanding of the present invention.

[0031] It will be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it will be further understood that, based on the principle that the inventor can appropriately define the meanings of words or terms to best interpret the present invention, the words or terms should be interpreted as having meanings consistent with their meanings in the context of the relevant technology and the technical concept of the present invention.

[0032] Generally, a silica wet gel produced using water glass has a form in which pores are filled with water as a solvent, and when the solvent is simply dried and removed, the solvent in the liquid phase evaporates into a gas phase and due to the high surface tension of water at the gas / liquid interface, the pore structure is likely to shrink and crack, resulting in a reduction in surface area and a change in pore structure. Therefore, in order to maintain the pore structure of the wet gel, it is necessary to replace the water with a relatively low surface tension with an organic solvent, and a technology for washing and drying the wet gel without causing its shrinkage while maintaining its structure is required.

[0033] In addition, the dried silica aerogel maintains a low thermal conductivity immediately after drying, but has a disadvantage of gradually increasing thermal conductivity due to the hydrophilicity of the silanol groups (Si—OH) on the silica surface absorbing water in the air.

[0034] Therefore, in order to reduce the shrinkage and cracking of the pore structure caused by the high surface tension of water at the air / liquid interface when drying the silica wet gel, and to maintain low thermal conductivity by reducing the water absorption of the dried silica aerogel, it is necessary to modify the surface of the silica aerogel to be hydrophobic. Therefore, the method of modifying the surface of the silica aerogel to be hydrophobic using a surface modifier has been widely used.

[0035] In order to modify the wet gel to be hydrophobic, one or more surface modifiers selected from the group consisting of trimethylchlorosilane (TMCS), hexamethyldisilazane (HMDS), dimethyldiethoxysiloxane (DMDES), hexamethyldisiloxane (HMDSO) and trimethylethoxysilane (TMES) are generally used.

[0036] When hexamethyldisilazane (HMDS), dimethyldiethoxysiloxane (DMDES), hexamethyldisiloxane (HMDSO) or trimethylethoxysilane (TMES) is used in the above-mentioned surface modifier, the surface modifier is not mixed with water and thus has no reactivity with a wet gel, particularly a hydrogel obtained by gelling water glass, thereby performing a process in which the hydrogel is first converted into an organogel by solvent replacement using an amphiphilic organic solvent such as ethanol, and then surface-modified into a hydrophobic group by reacting with the surface modifier. However, in the case of this method, there are disadvantages in that a long time is required for solvent replacement to convert the hydrogel into the organogel, and a large amount of diluted organic solvent is generated.

[0037] In addition, when trimethylchlorosilane (TMCS) is used in the above-mentioned surface modifier, the surface modifier has reactivity with wet gel or hydrogel, and thus a solvent-free replacement process is possible, but there is a disadvantage in that all remaining trimethylchlorosilane after surface modification is converted into hexamethyldisiloxane (HMDSO) and inactivated. Therefore, in order to overcome the disadvantages of using trimethylchlorosilane (TMCS) alone, a method has been developed in which trimethylchlorosilane (TMCS) and hexamethyldisiloxane (HMDSO) are mixed in a small ratio and used, thereby performing surface modification by converting hexamethyldisiloxane, which is an inert substance, into trimethylchlorosilane using HCl generated from trimethylchlorosilane as a catalyst.

[0038] However, in both the method of using trimethylchlorosilane and the method of mixing trimethylchlorosilane with hexamethyldisiloxane (HMDSO), as shown in Reaction Formula 1, trimethylchlorosilane generates HCl after the surface modification reaction, so there is a problem that some chlorine remains in the finally obtained silica aerogel felt, causing corrosion (corrosion under insulation (CUI)).

[0039] Meanwhile, instead of using a method of mixing trimethylchlorosilane with hexamethyldisiloxane (HMDSO), a method of introducing HCl used as a catalyst alone into hexamethyldisiloxane is also used, and in this method, surface modification is achieved while hexamethyldisiloxane fills the pores, thereby converting the hydrogel into an organic gel, but similarly, some of the introduced chlorine remains in the finally obtained silica aerogel felt.

[0040] [Reaction 1]

[0041]

[0042] Meanwhile, the method for manufacturing the silica aerogel felt of the present invention does not use a chlorine (Cl)-containing compound during the manufacturing process, so the manufactured hydrophobic silica aerogel felt does not contain residual chlorine.

[0043] The method for manufacturing a silica aerogel felt of the present invention is characterized in that it includes: 1) preparing a silica sol containing a water glass solution; 2) impregnating the silica sol into a felt substrate; 3) preparing a wet gel by gelling the silica sol while the silica sol is impregnated into the felt substrate; 4) immersing the wet gel in an acid mixture aqueous solution containing an acetic acid and nitric acid aqueous solution, and surface-modifying the wet gel with an alkyl disiloxane compound; and 5) drying the surface-modified wet gel, wherein, after the above step 4), the acetic acid concentration (w / w) is 30% to 90%, and the nitric acid concentration (w / w) is 5% to 10%.

[0044] The method for manufacturing the silica aerogel felt of the present invention uses acetic acid and nitric acid. Acetic acid is an amphiphilic substance that is soluble in water and in alkyldisiloxane compounds used as surface modifiers. Nitric acid can promote the protonation of alkyldisiloxane compounds. The amounts of acetic acid and nitric acid used are such that after the surface modification in the above step 4), the concentration of acetic acid and the concentration of nitric acid [weight (W) / weight (W)] each meet a predetermined value, thereby exhibiting an excellent surface modification rate and making the finally manufactured silica aerogel felt free of residual chlorine.

[0045] 1) Preparation of silica sol containing water glass solution

[0046] The silica sol of the above step 1) can be prepared by mixing a water glass solution as a silica precursor and an acid catalyst.

[0047] In the silica sol, the acid catalyst may be included in a molar ratio of 1 to 3 with respect to the water glass in the water glass solution.

[0048] The water glass solution may be a diluted solution obtained by adding and mixing distilled water to water glass, and the water glass may be sodium silicate (Na2SiO3), which is an alkali metal silicate obtained by melting silicon dioxide (SiO2) and an alkali.

[0049] The water glass dispersion may contain 1 to 13 wt % of silicon dioxide (SiO2). If silicon dioxide is contained in the water glass dispersion solution at a content lower than the above range, aerogel may not be properly formed, and when silicon dioxide is contained at a content higher than the above range, gelation may be unfavorable, or the specific surface area may be reduced.

[0050] As the acid catalyst, any one or more of organic acids and inorganic acids that do not contain chlorine in the molecular structure of the compound can be used to prevent the final silica aerogel felt from containing chlorine. For example, the acid catalyst can be one or more selected from the group consisting of acetic acid, oxalic acid, nitric acid, sulfuric acid and hydrofluoric acid. Specifically, considering the acid mixture aqueous solution used in the surface modification of the above step 4), nitric acid, acetic acid or a mixture thereof can be used.

[0051] The acid catalyst may be contained in an amount such that the pH of the silica sol is 3 to 10. If the pH of the silica sol is out of the above range, gelation in step 3) may be impaired, or the gelation rate may be too fast or too slow, so that processability may be reduced.

[0052] 2) Impregnation of silica sol into felt substrate

[0053] The above step 2) is a step of impregnating the silica sol into the felt base material.

[0054] In terms of improving the thermal insulation of the silica aerogel felt, the felt substrate of the embodiment of the present invention can be specifically a porous substrate. When a porous felt substrate is used, the silica sol easily penetrates into the substrate, thereby uniformly forming an aerogel inside the felt substrate, so that the manufactured silica aerogel felt can have excellent thermal insulation.

[0055] The felt substrate that can be used according to an embodiment of the present invention can be a film, a sheet, a net, a fiber, a foam, a nonwoven body or a laminate of two or more thereof. Moreover, according to the purpose of the felt substrate, a surface roughness can be formed or patterned on its surface. More specifically, the felt substrate can be a fiber that can further improve thermal insulation by including a space or a gap (whereby a silica aerogel can be easily inserted into the felt substrate). In addition, the felt substrate can preferably have a low thermal conductivity.

[0056] Specifically, the felt substrate may be polyamide, polybenzimidazole, aromatic polyamide, acrylic resin, phenolic resin, polyester, polyetheretherketone (PEEK), polyolefin (e.g., polyethylene, polypropylene or copolymers thereof), cellulose, carbon, cotton, wool, hemp, nonwoven fabric, glass fiber or ceramic wool, etc. More specifically, the felt substrate in the present invention may be glass fiber.

[0057] In addition, according to an embodiment of the present invention, the impregnation can be performed by pouring the silica sol into a reaction vessel containing the felt substrate or by wetting the felt substrate with the silica sol. At this time, in order to improve the bonding of the felt substrate with the silica sol, the felt substrate can be gently pressed down to fully impregnate it. Thereafter, the felt substrate can be pressed to a predetermined thickness at a constant pressure to remove excess silica sol, thereby reducing the drying time.

[0058] 3) When the silica sol is impregnated into the felt substrate, the silica sol is gelled to form a felt substrate. Prepare wet gel

[0059] The above step 3) is a step of producing a hydrophobic silica wet gel felt, and the wet gel felt can be produced by allowing the silica sol impregnated in the felt base material to stand to undergo gelation.

[0060] Here, the gelation may be a sol-gel reaction, and the "sol-gel reaction" may be the formation of a network structure from a silicon unit precursor material.

[0061] Here, the network structure may be a planar grid structure in which specific polygons having one or more atomic arrangements are connected to each other, or a structure in which specific polyhedrons share their vertices, edges, faces, etc. with each other to form a three-dimensional skeleton structure.

[0062] The production method according to the embodiment of the present invention may further include a step of aging the silica wet gel felt produced after the gelation in the above step 3).

[0063] The aging is not particularly limited, but can be performed, for example, by leaving it to stand at a temperature of room temperature (25° C.) to 90° C. for 1 hour to 24 hours.

[0064] The manufacturing method according to the embodiment of the present invention performs aging after manufacturing the silica wet gel felt, so that the network structure of the wet gel in the silica wet gel felt can be formed more firmly, and thus the pore properties can be excellent.

[0065] 4) The wet gel was immersed in an acid mixture aqueous solution containing acetic acid and nitric acid aqueous solution and alkyl disiloxane was used to Surface modification with compounds

[0066] In the above step 4), the following process is performed, wherein the wet gel is immersed in an acid mixture aqueous solution containing acetic acid and nitric acid aqueous solutions, and surface-modified with an alkyl disiloxane compound, thereby forming a hydrophobic silica wet gel felt.

[0067] In one embodiment of the present invention, a process of adding the acid mixture aqueous solution to the wet gel to immerse the wet gel in the acid mixture aqueous solution and then adding the alkyl disiloxane compound to the wet gel may be performed, and in another embodiment of the present invention, a process of simultaneously adding the acid mixture aqueous solution and the alkyl disiloxane compound to the wet gel may be performed.

[0068] Regardless of the addition time of the acid mixture aqueous solution and the alkyldisiloxane compound added to the wet gel, the acid mixture aqueous solution containing water having a higher density than the alkyldisiloxane compound is positioned downward, thereby achieving layer separation of the alkyldisiloxane compound layer at the upper part and the acid mixture aqueous solution layer at the lower part. Even when the process of adding the acid mixture aqueous solution and the alkyldisiloxane compound together to the wet gel is performed, the hydrophobic alkyldisiloxane compound and the acid mixture aqueous solution containing water are separated into different layers, and the wet gel containing water is located in the acid mixture aqueous solution layer, thereby performing the impregnation of the acid mixture aqueous solution.

[0069] In the process that wet gel is immersed in the acid mixture aqueous solution, the acid mixture aqueous solution enters the wet gel by diffusion, so that the moisture existing in the wet gel comes out from the wet gel and moves to the acid mixture aqueous solution layer. As mentioned above, when the dipping of the acid mixture aqueous solution is completed, the acid concentration of the acid mixture aqueous solution in the wet gel inside and the wet gel outside can be in balance.

[0070] Acetic acid as amphiphilic substance contained in the acid mixture aqueous solution allows trace alkyl disiloxane compounds to dissolve in the acid mixture aqueous solution at the interface between the alkyl disiloxane compounds layer and the acid mixture aqueous solution layer, thereby realizing the surface modification of wet gel by alkyl disiloxane compounds.In the process realizing the surface modification of wet gel, the aqueous solution of filling wet gel is replaced with alkyl disiloxane compounds, so that wet gel is filled with alkyl disiloxane compounds, and the aqueous solution flows out of wet gel and moves to the acid mixture aqueous solution layer.When the impregnation process and the surface modification process are completed, the acid concentration inside the wet gel and the acid concentration outside the wet gel are in balance.

[0071] The wet gel contains water and thus is initially located in the acid mixture aqueous solution layer, and as the wet gel is filled with the alkyldisiloxane compound as surface modification is achieved, the wet gel gradually rises and moves to the alkyldisiloxane compound layer.

[0072] In one embodiment of the present invention, when hexamethyldisiloxane is used as the alkyldisiloxane compound in the above step 4), the reaction shown in the following reaction formula 2 may be performed.

[0073] [Reaction 2]

[0074]

[0075] The acetic acid concentration (w / w) after the above-mentioned step 4) refers to the concentration of the acetic acid included in the acid mixture aqueous solution layer after the above-mentioned step 4), and can be represented by the following mathematical formula 1. The concentration of acetic acid can be calculated by measuring the weight of the water in the acid mixture aqueous solution layer after the above-mentioned step 4) and measuring the weight of the acetic acid in the acid mixture aqueous solution layer by gas chromatography (GC). The weight of the water in the acid mixture aqueous solution layer can be measured using a Karl Fischer moisture meter (SiAnalytics Titro Line 7000).

[0076] [Mathematical formula 1]

[0077] Acetic acid concentration (w / w) = weight of acetic acid in the acid mixture aqueous solution layer / (weight of acetic acid in the acid mixture aqueous solution layer + total weight of water in the acid mixture aqueous solution layer) × 100

[0078] In addition, the nitric acid concentration (w / w) after the above step 4) refers to the concentration of nitric acid contained in the acid mixture aqueous solution layer after the above step 4), and can be expressed by the following mathematical formula 2. The concentration of nitric acid can be calculated by measuring the weight of water in the acid mixture aqueous solution layer after the above step 4) and measuring the weight of nitric acid in the acid mixture aqueous solution layer, at this time, the amount of nitric acid after the above step 4) is the same as the amount of nitric acid added when preparing the acid mixture aqueous solution.

[0079] [Mathematical formula 2]

[0080] Nitric acid concentration (w / w) = weight of added nitric acid / (weight of added nitric acid + total weight of water in the acid mixture aqueous solution layer) × 100

[0081] As described above, when the immersion process in the acid mixture aqueous solution is completed, the acid concentration inside the wet gel and the acid concentration outside the wet gel are in equilibrium, so when the acid concentration of the acid mixture aqueous solution layer after immersion is measured, the acid concentration inside the wet gel can be confirmed, and thus the acid concentration involved in the surface modification can be determined.

[0082] After the above step 4), the water contained in the acid mixture aqueous solution layer may be water contained in the acetic acid aqueous solution and the nitric acid aqueous solution, water contained in the wet gel, and water remaining after the above step 4) in the water derived from the hydrophilic-hydrophobicization reaction of the wet gel, and the total weight thereof may be the total weight of the water in the acid mixture aqueous solution layer.

[0083] The above step 4) can be performed by the following method, wherein after the process of immersing the wet gel in the acid mixture aqueous solution is completed, the process of surface modification with an alkyl disiloxane compound is sequentially performed.

[0084] After the above step 4), the acetic acid concentration (w / w) may be 30% to 90%, specifically 35% to 80%, 36% to 80%, and more specifically 36% to 78%. When the amount of acetic acid used is such that the concentration of acetic acid after the above step 4) is 30% to 90%, the acetic acid can enable the hydrophilic wet gel to effectively contact the hydrophobic alkyl disiloxane compound, thereby smoothly achieving the surface modification reaction. When the acetic acid concentration (w / w) is low, the reaction between the hydrophilic wet gel and the hydrophobic alkyl disiloxane compound may not proceed, and thus the surface modification reaction may not be smoothly achieved. In addition, if the acetic acid concentration is too high, more acetic acid than required should be introduced, which may reduce economic feasibility.

[0085] In addition, after the above step 4), the nitric acid concentration (w / w) can be 5% to 10%, specifically 5% to 9%, 5% to 8%, 5.5% to 8%, 5.5% to 7.5%, and more specifically 5.5% to 7.3%. When the nitric acid concentration meets the above range, the protonation of the alkyl disiloxane compound is effectively promoted, so that an excellent surface modification reaction rate can be exhibited. When the nitric acid concentration is too low, the surface modification reaction rate decreases, and the surface modification reaction of the alkyl disiloxane compound cannot be fully realized, so that the hydrophobicity of the wet gel is reduced, and therefore, the thermal conductivity of the silica aerogel felt finally manufactured may increase. In addition, when the nitric acid concentration is too high, the oxidizing ability of nitric acid increases, and dangerous side reactions are formed by reacting with acetic acid, which may reduce stability.

[0086] The method for manufacturing silica aerogel felt according to an embodiment of the present invention ensures that the acid mixture aqueous solution satisfies the weight ratio of acetic acid to nitric acid when the wet gel is immersed in the acid mixture aqueous solution in the above step 4), and confirms whether the acetic acid concentration and the nitric acid concentration after the above step 4) meet the above values, thereby quickly and fully effectively achieving surface modification of the wet gel, especially the hydrogel prepared by using a water glass solution.

[0087] The alkyldisiloxane-based compound may be introduced in a volume ratio of 1 to 3 times, specifically 1 to 2.5 times, more specifically 1 to 2 times, based on the volume of the wet gel.

[0088] In order to modify the wet gel and replace the solvent of the wet gel, the alkyldisiloxane compound needs to be introduced in a volume of more than 1 times the volume of the wet gel, and when the amount of the alkyldisiloxane compound introduced increases, the size of the equipment needs to be increased, so the alkyldisiloxane compound can be introduced within the above numerical range based on the volume of the wet gel.

[0089] The alkyl disiloxane compound may be a hexaalkyl disiloxane compound, specifically hexa(C 1-8 alkyl) disiloxane, more specifically, hexamethyl disiloxane.

[0090] The surface modification reaction may be performed at a temperature of 25° C. to 95° C. In addition, a stirring process may be performed during the process of immersing the wet gel in the acid mixture aqueous solution and the process of surface-modifying the wet gel with the alkyldisiloxane compound.

[0091] At this time, stirring is not particularly limited, but may be performed at a rate of 50 rpm to 700 rpm, for example.

[0092] In addition, step 4) of the embodiment of the present invention may be performed for 2 to 24 hours, and may preferably be performed for 4 to 22 hours, or 8 to 20 hours in terms of improving the economic feasibility of the process while maintaining the effect of surface modification at an excellent level.

[0093] In the manufacturing method of the embodiment of the present invention, when the above step 4) is performed by sequentially performing the process of surface modification with an alkyl disiloxane compound after the process of immersing the wet gel in the acid mixture aqueous solution is completed, the process of immersing in the acid mixture aqueous solution can be performed for 30 minutes to 4 hours, specifically 30 minutes to 3 hours, more specifically 1 hour to 3 hours, and the process of surface modification with an alkyl disiloxane compound can be performed for 1 hour and 30 minutes to 20 hours, specifically 3 hours to 19 hours, more specifically 6 hours to 18 hours.

[0094] 5) Drying the surface-modified wet gel

[0095] The above step 5) is a step of preparing a hydrophobic silica aerogel felt by drying the hydrophobic silica wet gel felt.

[0096] At this time, a washing step may be further performed before drying. Washing is to obtain a high-purity hydrophobic silica aerogel felt by removing impurities (sodium ions, non-reactants and by-products, etc.) generated during the reaction, wherein the washing can be performed by adding a non-polar organic solvent to the hydrophobic silica wet gel and stirring the mixture for 20 minutes to 1 hour, but is not limited thereto.

[0097] Drying may be performed by methods such as atmospheric pressure drying or supercritical drying, but is not limited thereto. As an example, atmospheric pressure drying may be a method of drying at a temperature of 100° C. to 190° C. under atmospheric pressure for 1 to 12 hours, and supercritical drying is a method of using CO2 in a supercritical state, wherein atmospheric pressure drying may have the advantages of being relatively simple and economical, and supercritical drying may have the advantage of effectively removing the fluid inside the gel.

[0098] The method for manufacturing the hydrophobic silica aerogel felt of the embodiment of the present invention can greatly improve the surface modification efficiency, and thus can have physical properties such as excellent pore properties and high hydrophobicity, and therefore, can ensure that the thermal insulation is at an excellent level. In particular, in the method for manufacturing the silica aerogel felt of the embodiment of the present invention, the hydrophobization of the aerogel is carried out under chlorine-free (Cl-free) conditions, so the silica aerogel felt finally manufactured can be free of chlorine or contain a minimum amount of chlorine, thereby eliminating the possibility that the part to which the silica aerogel felt is applied is corroded by chlorine.

[0099] The silica aerogel felt according to an embodiment of the present invention has a thermal conductivity of 12 to 19 mW / mK and a Cl content of 0 to 500 ppm.

[0100] Specifically, the thermal conductivity of the silica aerogel felt of an embodiment of the present invention can be greater than 12 mW / mK, greater than 13 mW / mK, greater than 14 mW / mK, greater than 15 mW / mK, or greater than 16 mW / mK, and less than 19 mW / mK, less than 18.5 mW / mK, or less than 18.3 mW / mK.

[0101] The silica aerogel felt of the embodiment of the present invention does not contain Cl derived from aerogel, but may contain a small amount of Cl derived from the felt substrate of the silica aerogel. Specifically, the Cl content of the silica aerogel felt of the embodiment of the present invention may be 0 ppm to 500 ppm, 0 ppm to 400 ppm, 0 ppm to 300 ppm, or 0 ppm to 200 ppm.

[0102] The silica aerogel felt manufactured by the manufacturing method according to an embodiment of the present invention can be used in various applications, including thermal insulation applications, including, for example, applications requiring thermal insulation at temperatures below 650°C. For example, the silica aerogel felt can be used as a thermal insulation material for pipes such as double-cased pipes, for thermal insulation of aircraft and parts thereof, thermal insulation of buildings, thermal insulation of spacecraft, thermal insulation of automobiles, thermal insulation of clothing, thermal insulation of shoes, etc. The aerogel felt can be used in the same manner as the case of using an aerogel mat or a plurality of aerogels.

[0103] Hereinafter, the present invention will be described in more detail with reference to Examples and Experimental Examples. However, the following Examples and Experimental Examples are merely illustrative of the present invention and are not intended to limit the scope of the present invention.

[0104] Example 1

[0105] 33.8 g of water glass was diluted in 108.1 g of water to prepare a water glass solution, and 7.8 g of acetic acid (≥97%) was added thereto to prepare a silica sol. The silica sol was impregnated into glass fiber and then left to stand for 10 minutes to obtain a glass fiber composite impregnated with a wet gel.

[0106] An acid mixture aqueous solution prepared by mixing 140 g of acetic acid (≥97%) and 15 g of a 70% (w / w) nitric acid aqueous solution was poured into the glass fiber impregnated with the wet gel, and the glass fiber was immersed in the acid mixture aqueous solution for 2 hours in an oven at 60° C. while maintaining the temperature, and then 160 g of hexamethyldisiloxane (HMDSO) was added thereto to perform a surface modification reaction in an oven at 75° C. while maintaining the temperature for 16 hours.

[0107] The manufactured hydrophobic silica wet gel felt was recovered and then completely dried in a forced circulation dryer at 150° C. for 4 hours to manufacture a hydrophobic silica aerogel felt.

[0108] Example 2

[0109] A hydrophobic silica aerogel felt is manufactured in the same manner as in Example 1, except that the content of acetic acid (≥97%) is changed to 185 g when preparing the acid mixture aqueous solution in the above Example 1, and a dilute nitric acid aqueous solution prepared by mixing 20 g of a 70% (w / w) nitric acid aqueous solution with 95 g of water is used instead of the 70% (w / w) nitric acid aqueous solution.

[0110] Example 3

[0111] A hydrophobic silica aerogel felt is manufactured in the same manner as in Example 1, except that the content of acetic acid (≥97%) is changed to 280 g when preparing the acid mixture aqueous solution in the above Example 1, and a dilute nitric acid aqueous solution prepared by mixing 30 g of a 70% (w / w) nitric acid aqueous solution with 142 g of water is used instead of the 70% (w / w) nitric acid aqueous solution.

[0112] Example 4

[0113] A hydrophobic silica aerogel felt was manufactured in the same manner as in Example 1, except that the content of acetic acid (≥97%) was changed to 80 g when preparing the acid mixture aqueous solution in Example 1.

[0114] Example 5

[0115] A hydrophobic silica aerogel felt was manufactured in the same manner as in Example 1, except that the content of acetic acid (≥97%) was changed to 500 g when preparing the acid mixture aqueous solution in Example 1.

[0116] Comparative Example 1

[0117] A hydrophobic silica aerogel felt was produced in the same manner as in Example 1, except that only 140 g of 35 wt % hydrochloric acid was used instead of the acid mixture aqueous solution mixed with acetic acid and nitric acid aqueous solutions in the above Example 1.

[0118] Comparative Example 2

[0119] A hydrophobic silica aerogel felt was manufactured in the same manner as in Example 1, except that only 140 g of acetic acid (≥97%) was used instead of the acid mixture aqueous solution mixed with acetic acid and nitric acid aqueous solutions in the above Example 1.

[0120] Comparative Example 3

[0121] A hydrophobic silica aerogel felt was produced in the same manner as in Example 1, except that only 140 g of a 70% (w / w) nitric acid aqueous solution was used instead of the acid mixture aqueous solution of acetic acid and nitric acid aqueous solution.

[0122] Comparative Example 4

[0123] A hydrophobic silica aerogel felt is manufactured in the same manner as in Example 1, except that a dilute nitric acid aqueous solution prepared by mixing 15 g of a 70% (w / w%) nitric acid aqueous solution with 71.3 g of water is used together with 140 g of acetic acid (≥97%) instead of the 70% (w / w%) nitric acid aqueous solution when preparing the acid mixture aqueous solution in the above Example 1.

[0124] Comparative Example 5

[0125] A hydrophobic silica aerogel felt is manufactured in the same manner as in Example 1, except that a dilute nitric acid aqueous solution prepared by mixing 20 g of a 70% (w / w%) nitric acid aqueous solution with 100 g of water and 70 g of acetic acid (≥97%) are used instead of the 70% (w / w%) nitric acid aqueous solution when preparing the acid mixture aqueous solution in the above Example 1.

[0126] Comparative Example 6

[0127] A hydrophobic silica aerogel felt was produced in the same manner as in Example 1, except that the amount of the 70% (w / w) nitric acid aqueous solution used was changed to 30 g when preparing the acid mixture aqueous solution in Example 1.

[0128] The amounts of components added during each surface modification reaction in Examples 1 to 5 and Comparative Examples 1 to 6 described above are shown in Table 1 below.

[0129] [Table 1]

[0130]

[0131] Experimental example

[0132] 1) Acetic acid concentration after immersion

[0133] In each of Examples 1 to 5 and Comparative Examples 1 to 6, the weight of water in the acid mixture aqueous solution after the acid impregnation was measured using a Karl Fischer moisture meter (Si Analytics Titro Line 7000).

[0134] The amount of acetic acid in the obtained acid mixture aqueous solution after the acid impregnation was analyzed using gas chromatography (GC).

[0135] -Column: AT-1000

[0136] -Gas flow rate: column (He) 4mL / min

[0137] - Oven temperature: Initial value and time 40°C, 5 minutes

[0138] - Injector temperature: 250℃

[0139] -Detector temperature: 270℃

[0140] Acetic acid concentration after acid immersion = weight of acetic acid / (weight of acetic acid + weight of water) × 100

[0141] 2) Nitric acid concentration after acid immersion

[0142] In each of Examples 1 to 5 and Comparative Examples 1 to 6, the weight of water in the acid mixture aqueous solution after the acid impregnation was measured using a Karl Fischer moisture meter (Si Analytics Titro Line 7000).

[0143] Since the amount of nitric acid in the acid mixture aqueous solution after acid impregnation is the same as the amount of nitric acid initially introduced, the nitric acid concentration is calculated by taking the weight of nitric acid initially introduced as the weight of nitric acid in the acid mixture aqueous solution.

[0144] Nitric acid concentration after acid leaching = weight of nitric acid introduced / (weight of nitric acid introduced + weight of water)

[0145] 3) Measurement of thermal conductivity (mW / mK)

[0146] The room temperature (about 23° C.) thermal conductivity of the silica aerogel felt produced in each of Examples 1 to 5 and Comparative Examples 1 to 6 was measured using HFM 436 equipment from NETZSCH Co.

[0147] 4) Measurement of Cl residual

[0148] The amount of residual Cl of the silica aerogel felt produced in each of Examples 1 to 5 and Comparative Examples 1 to 6 was measured using a combustion ion chromatography (IC) system (AQF-2100H, ICS-3000, Thermo Fisher Scientific Co.).

[0149] [Table 2]

[0150]

[0151] Examples 1 to 5 manufactured silica aerogel felt by using an acid mixture aqueous solution comprising acetic acid and nitric acid aqueous solution, wherein the acetic acid concentration (w / w) of the acid mixture aqueous solution layer after acid impregnation satisfies 30% to 90% and the nitric acid concentration (w / w) satisfies 5 to 10%, and it was confirmed that silica aerogel felt with low thermal conductivity was manufactured.

[0152] Comparative Example 1 used hydrochloric acid (HCl) as an acid, in which 5,000 ppm or more of Cl was detected in the manufactured silica aerogel felt, and compared with Examples 1 to 3, the thermal conductivity value was relatively slightly higher.

[0153] Comparative Example 2 is an example in which only acetic acid is used without nitric acid, and it is confirmed that the thermal conductivity increases due to the slow surface modification rate, resulting in deterioration of physical properties. In addition, Comparative Example 3 is an example in which only nitric acid is used without acetic acid, in which no reaction occurs between hexamethyldisiloxane and wet gel, since acetic acid as an amphiphilic solvent is not used, and thus the surface modification is not performed at all, and thus high thermal conductivity is exhibited.

[0154] In addition, Comparative Example 4 is an example in which the nitric acid concentration of the acid mixture aqueous solution layer after acid impregnation is less than 5%, and Comparative Example 5 is an example in which the acetic acid concentration of the acid mixture aqueous solution layer after acid impregnation is less than 30%, wherein the amount of nitric acid and acetic acid used in the acid mixture aqueous solution is less than the appropriate amount, thereby confirming that the manufactured silica aerogel felt exhibits a high thermal conductivity value and deteriorates in physical properties.

[0155] Meanwhile, Comparative Example 6 is an example in which the nitric acid concentration in the acid mixture aqueous solution layer after acid impregnation is 10% or more despite the simultaneous use of acetic acid and nitric acid, wherein the amount of nitric acid used is greater than the appropriate amount, resulting in a side reaction between acetic acid and nitric acid, thereby not causing a reaction for surface modification of the wet gel.

Claims

1. A method for producing a silica aerogel felt, the method comprising the following steps: 1) preparing a silica sol containing a water glass solution; 2) impregnating the silica sol into a felt substrate; 3) preparing a wet gel by gelling the silica sol while the silica sol is impregnated into the felt substrate; 4) immersing the wet gel in an acid mixture aqueous solution containing acetic acid and nitric acid aqueous solution, and surface-modifying the wet gel with an alkyl disiloxane compound; and 5) drying the surface-modified wet gel, Wherein, after the above step 4), the concentration of acetic acid is 30 wt % to 90 wt %, and the concentration of nitric acid is 5 wt % to 10 wt %.

2. The method for producing a silica aerogel felt according to claim 1, wherein: The acetic acid concentration is 35 wt % to 80 wt %.

3. The method for producing a silica aerogel felt according to claim 1, wherein: The nitric acid concentration is 5.5 wt % to 8 wt %.

4. The method for producing a silica aerogel felt according to claim 1, wherein: In the above step 4), after the process of immersing the wet gel in the acid mixture aqueous solution is completed, the process of surface modification with the alkyl disiloxane compound is sequentially performed.

5. The method for producing a silica aerogel felt according to claim 1, wherein: In the above step 4), the acid mixture aqueous solution and the alkyl disiloxane compound are introduced into the wet gel in sequence, or the acid mixture aqueous solution and the alkyl disiloxane compound are introduced into the wet gel at the same time.

6. The method for producing a silica aerogel felt according to claim 1, wherein: In the above step 4), the alkyl disiloxane compound is added in a volume ratio of 1 to 3 times based on the volume of the wet gel.

7. The method for producing a silica aerogel felt according to claim 1, wherein: The alkyl disiloxane compound is hexa(C 1-8 alkyl) disiloxane.

8. The method for producing a silica aerogel felt according to claim 1, wherein: The method for manufacturing the silica aerogel felt is carried out under chlorine-free conditions.

9. A silica aerogel felt having a thermal conductivity of 12 to 19 mW / mK and a Cl content of 0 to 500 ppm.

10. The silica aerogel felt according to claim 9, wherein: The silica aerogel felt has a Cl content of 0 ppm to 200 ppm.

Citation Information

Patent Citations

  • Lifting belts to prevent injury

    KR1020220091299A

  • Aerogel composites, process for producing the same and their use

    US5789075A